"We all deserve justice": Perspectives on being arrested for aggravated prostitution. Issue 3 (3rd July 2021) - Lennon-Dearing, Robin; Hirschi, Melissa; Dill, Sarah; Gore, Kayla
Abstract: Aggravated prostitution is the combination of one stigmatizing circumstance accompanying another: prostitution and living with HIV. This HIV criminal offense disproportionally impacts African Americans, women, transgender and gender non-conforming people, people experiencing homelessness, and people unable to meet their basic needs. Punishment for aggravated prostitution is unduly harsh and inconsistent with the harm caused. This article describes the findings from a qualitative descriptive study of fourteen individuals who share their experiences of what has happened as a result of being arrested for aggravated prostitution. Findings include (a) economic survival and discrimination are reasons given for sex work, (b) people with stigmatized intersectional social identities experience police profiling, discrimination, and harassment, (c) those arrested for aggravated prostitution are punished severely and permanently, and (d) these findings support policy action. Modernizing HIV criminal laws should be accompanied by the provision of community services and supports as an alternative to arresting people for aggravated prostitution.